Infection with respiratory syncytial virus influences FasL-mediated apoptosis of pulmonary γδ T cells in a murine model of allergen sensitization. (May 2014) - Zeng, Sheng; Wu, Jianqi; Liu, Jing; Qi, Feifei; Kimura, Yoshinobu; Cao, Yaming; Liu, Beixing
Abstract Background: It has been reported that adoptive transfer of γδ T cells increases the cellular infiltration, especially eosinophils, in the lungs of allergic mice, suggesting that γδ T cells may play a proinflammatory role in allergic airway inflammation. Respiratory syncytial virus (RSV) infection can decrease the number of Th2-type γδ T cells. However, the underlying mechanisms remain unknown. Methods: BALB/c mice were inoculated intranasally with RSV before or after sensitization to OVA. The amounts of Th1/Th2 cytokines as well as the levels of specific antibodies were determined by ELISA. The apoptotic death of pulmonary γδ T cells was analyzed by flow cytometry. Results: Adoptive transfer of γδ T cells increased the production of Th2 cytokines in the lungs and allergy-related antibodies in the serum, further confirming that γδ T cells act as pro-inflammatory cells or a promoter for the development of allergic asthma. RSV infection before sensitization to OVA enhanced apoptotic death of pulmonary γδ T cells. The percentage and absolute number of FasL-expressing γδ T cells in the lungs of allergic mice were elicited significantly by prior RSV infection. Blocking FasL with monoclonal antibody diminished apoptotic death of γδ T cells, suggesting that FasL is important for RSV-induced apoptosis of pulmonary γδ T cells. Conclusions: This work provides evidence that RSV infection suppresses the subsequent development of OVA-induced allergic responses partly by enhancing FasL-mediated apoptosis of pulmonary γδ T cells.